A Business Design of Jannat Kitchen - Al-Sabahi, Gehad Rashed Mansoor; Panuntun, Bagus (Selekta Manajemen: Jurnal Mahasiswa Bisnis & Manajemen, 2024)
Indonesia is a country that has a high tolerance for cultural differences. Strong cultural acculturation in Indonesian society gives rise to new preferences for various things related to culture, including culinary. Jannat Kitchen’s founder saw this as a real business opportunity. Jannat Kitchen was established to tap into the growing market demand for Arabian food in Indonesia. The business was committed to provide high-quality and authentic Arabian food, affordable, and carefully curated taste for the customers. Jannat Kitchen prioritizes the use of high-quality ingredients sourced originally from local and imported from Arabian countries and original Yemeni chefs and staff members to ensure the authenticity of the flavour of the food and the sense of the culinary culture. The business is located in the area of Ma’had Tahfidzul Qur’an Isy Karima, Jl. Raya Solo - Tawangmangu Jl. Pakel No.KM34, Popongan, Gerdu, Kec. Karangpandan, Kabupaten Karanganyar, Jawa Tengah 57791. During its implementation, Jannat Kitchen passed several problems with the main priority was marketing issues. PDCA-Method was used to analyze the problems. The use of social media marketing is less appropriate and does not suit consumer behavior so its application is less effective. Jannat Kitchen tried to execute traditional marketing to complete the social media marketing. The traditional marketing strategy implemented by Jannat Kitchen was successful and in accordance with the company’s milestones.